A Randomized, Controlled Trial of Gabapentin Enacarbil in Subjects with Neuropathic Pain Associated with Diabetic Peripheral Neuropathy. Issue 6 (27th November 2012) - Rauck, Richard; Makumi, Clare W.; Schwartz, Sherwyn; Graff, Ole; Meno‐Tetang, Guy; Bell, Christopher F.; Kavanagh, Sarah T.; McClung, Carrie L.
Abstract Background Gabapentin enacarbil (GEn), a transported prodrug of gabapentin, provides sustained, dose‐proportional gabapentin exposure. The purpose of this study was to investigate the dose response of GEn to select the optimal dose(s) for clinical use in subsequent diabetic peripheral neuropathy (DPN) trials. Methods This was a multicenter, randomized, double‐blind, double‐dummy, parallel group, placebo‐controlled trial with a study duration of approximately 20 weeks (Clinicaltrials.gov database, Identifier ! NCT00643760). Pregabalin (PGB) (Lyrica®; Pfizer Inc.) was used as an active control to provide assay sensitivity of the trial. A total of 421 adult subjects with DPN were randomized in a ratio of 2:1:1:1:2 to receive oral GEn 3, 600 mg/day, GEn 2, 400 mg/day, GEn 1, 200 mg/day, PGB 300 mg/day, or matching placebo, respectively. The primary efficacy endpoint was change from baseline to end of maintenance treatment with respect to the mean 24‐hour average pain intensity score based on an 11‐point Pain Intensity Numerical Rating Scale (PI‐NRS). Safety and tolerability assessments included treatment‐emergent adverse events (TEAEs), laboratory evaluations, vital signs, electrocardiograms (ECG), neurological examination, and pedal edema. Results The adjusted mean difference vs. placebo at the end of maintenance treatment with respect to the mean 24‐hour average PI‐NRS pain intensity score for GEn 1, 200 mg (−0.35; [95% CI: −1.02, 0.31]; P = 0.295), GEn 2, 400 mg (−0.02; [95% CI: −0.71, 0.66]; P = 0.946), and GEn 3, 600 mg (−0.55; [95% CI: −1.10, 0.01]; P = 0.105) was not statistically significant. The active control, PGB (300 mg/day), did not differentiate from placebo. Conclusion Overall, none of the GEn treatment groups differentiated from placebo. Analyses of the secondary endpoints showed comparable results across treatment groups. However, the majority of the endpoints, including all of the pain endpoints, showed the largest numerical treatment difference was between GEn 3, 600 mg and placebo. The active control, PGB (300 mg/day), did not differentiate from placebo.